Rationalism and criticism in the Qur’an: an analytical study from modern books of tafsir - Solihin, Sohirin Mohammad; Osmani, Noor Mohammad; Jani, Mohd. Shah (IIUM Press, International Islamic University Malaysia, 2017)
The paper attempts to reveal the significance on the use of intellect and criticism in Muslim theology to prove the validity of the revelation, particularly relating to truth and justice. This can be conducted by exploring the views of the mufassirËn and contemporary Muslim scholars in providing an exposition towards the Qur’Énic verses focusing on the prohibition of blind fanaticism. The emphasis is closely linked with Muslim activities with an attempt in achieving progress in their lives. We found that creative thinking and the use of intellect is inseparable from the concept of reading as reflected within the first revelation given to the Prophet (pbuh). It is to not simply read the text, rather, it deals with rationality to confirm, with the concept of the truth which may come from human thought. Hence, the revelation appeals to its adherents to observe the use of rationalism and criticism to confirm the validity of certain thought.